Strategi Branding Instagram Destinasi Wisata Umbul Songo Kabupaten Semarang Jawa Tengah - Ikhsanudinul Kahfi; Desika Nur Jannah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2026)
This study aims to analyze the Instagram branding strategy in promoting the Umbul Songo tourist destination in Semarang Regency. This research employed a descriptive qualitative method with a case study approach. Data were collected through observation, interviews with the destination manager, Instagram administrator, and tourists, documentation, and Instagram Insight analysis. The findings indicate that Instagram plays an important role in increasing destination visibility through visual-based content and digital promotion. Instagram Insight data recorded 940 impressions, consisting of 893 impressions from Instagram and 47 from Facebook. In addition, reels content showed higher engagement, increasing from 15% to 30%, indicating that short-form video content is more effective in attracting audience attention. Interview results revealed that Instagram influenced tourists' decisions to visit because the visual content reflected the actual conditions of the destination. The findings also show that Umbul Songo's branding strategy is strengthened by its natural conservation identity, local cultural values, and user-generated content shared by visitors. This study concludes that Instagram is an effective medium for destination branding; however, greater consistency in content management and audience engagement is needed to strengthen destination competitiveness. Keywords: destination branding, Instagram, tourism, digital marketing